HUBUNGAN KUALITAS PELAYANAN KELUHAN DENGAN KEPUASAN PELANGGAN - Oktha Fanny; Muslim Muslim; Mariana R.A. Siregar (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to identify the relationship between service quality complaints with customer satisfaction in the Bogor branch Transvision, to identify customer characteristics, and identify the relationship between variable customer characteristics with customer satisfaction in the Bogor branch Transvision.This research was conducted at Transvision Bogor branch in March 2017. Samples taken were 76 customers. The sampling technique is using probability sampling. Data sources used include primary data such as questionnaires, interviews, and observations, and secondary data, such as books, official sites related to research. Data analysis techniques used descriptive statistical analysis and non-parametric statistical analysis. Correlation test using the Chi-Square formula and Spearman Rank with validity test using the Pearson product moment formula. Analysis X1 regarding customer characteristics, variable X2 regarding the quality of Customer Relationship Management services, and the last variable Y1 is customer satisfaction in Bogor branch Transvision. The results of the correlation between customer characteristics X1 and customer satisfaction Y1 at Transvision Bogor branch get a low correlation value, which means that there is no relationship between the two variables X1 and Y1. While the value of the correlation between the quality of service X2 with the number of customers in Transvision Bogor branch Y1 get a high correlation value means that there is a relationship between the two variables X2 with Y1. Keywords: Service Quality, Service Satisfaction, Transvision